Right Heart Involvement in Patients with Sarcoidosis. Issue 5 (16th January 2016) - Patel, Mita B.; Mor‐Avi, Victor; Murtagh, Gillian; Bonham, Catherine A.; Laffin, Luke J.; Hogarth, Douglas Kyle; Medvedofsky, Diego; Lang, Roberto M.; Patel, Amit R.
Abstract : The left ventricle (LV) is affected in 20–25% of patients with sarcoidosis and its involvement is associated with morbidity and mortality. However, effects of sarcoidosis on the right ventricle (RV) are not well documented. Our aims were to investigate the prevalence of RV dysfunction in patients with sarcoidosis and determine whether it is predominantly associated with direct cardiac involvement, severity of lung disease, or pulmonary hypertension (PH). We identified 50 patients with biopsy‐proven extra‐cardiac sarcoidosis and preserved LV function, who underwent echocardiography, pulmonary function (PF) testing, and cardiovascular magnetic resonance. RV function was quantified by free wall longitudinal strain. Tricuspid valve Doppler and estimated right atrial pressure were used to estimate systolic pulmonary artery pressure. Myocardial late gadolinium enhancement was considered diagnostic for cardiac sarcoidosis and assumed to involve both ventricles. Of the 50 patients, 28 (56%) had RV dysfunction, 4 with poorly defined PF status. Of the remaining 24 patients, 16 (67%) had lung disease, 8 (33%) had PH, and 10 (42%) had LV involvement. Ten patients had greater than one of these findings, and 4 had all 3. In contrast, in 4/24 patients (17%), RV dysfunction could not be explained by these mechanisms, despite severely reduced RV strain. In conclusion, RV dysfunction is common in patients with sarcoidosis and is usually associated with either direct LV involvement, lung disease, or PH, but may occur in the absence of these mechanisms, suggesting the possibility of isolated RV involvement and underscoring the need for imaging protocols that would include RV strain analysis.